Tinjauan Hukum Islam terhadap Musibah Pandemi Covid-19 dan Implikasinya pada Sikap Umat dalam Menghadapi Wabah Covid-19 - Sasa Sunarsa (Prodi Hukum Ekonomi Syariah (Muamalah), 2021)
This paper aims to examine the Covid-19 outbreak from the perspective of the Koran based on Ibn Kathir's interpretation of the QS. al-Hadid: 22-23. The research approach used is qualitative with library research method. The results of the study show that Ibn Kathir when interpreting the QS. al-Hadid: 22-23 explains that disasters basically happen by the will of Allah SWT. and its occurrence was determined even before the creation of the universe. A correct understanding of the meaning of disaster can make it easier for humans to be patient, which can be used as an effective approach in strengthening mental resilience and making a person strong and resilient in the face of the Covid-19 outbreak. In addition, the commentary of Ibn Kathir can be applied in dealing with the Covid-19 outbreak, this Covid-19 disaster is God's destiny, and God's destiny must be good, and sunnah-kauniyah apply. Trying not to clash between aqidah and sharia, when there are differences regarding the implementation of worship in mosques in the midst of the Covid-19 outbreak.